Payment Facilitators and Their Role in Online E-Commerce Transactions - Qazi, H.M (International Journal of Computer Sciences and Engineering, 2018)
Electronic Commerce has revolutioned the entire way business is conducted and is being used in almost every sphere of activity. The true essence of electronic commerce stems from electronic payments- the facility to make and receive payments online. While customers crave for a variety of payment options, merchants manage to live up to the expectations, thanks to third-party payment service providers (PSPs), what the industry calls Payment Facilitators. A payment facilitator is an entity that acts as a seamless, integrated digital payment acceptance platform which receives customer payments on behalf of merchants. This relieves merchants from the burden of handling payments, along with a host of technical infrastructure, risk management and regulatory obligations. The current work provides a behind-the-curtain scenario of retail online payments and explains how a payment facilitator is the simplest way for online merchants to accept payments from their customers. Payment facilitators have yielded a new business model, which renders tremendous benefits to online businesses- both in terms of technology and procedures. All such benefits are visited.